Engineering aspects of the design, construction and performance of modular redox flow batteries for energy storage. (June 2017) - Arenas, L.F.; Ponce de León, C.; Walsh, F.C.
Graphical abstract: Highlights: The history and relevance of redox flow batteries in energy storage are highlighted. Electrochemical engineering principles of cell design and operation are summarised. Performance can be quantified at a known state of charge and modelled by multiphysics. Reaction environment can be described by dimensionless relationships. The importance of operational parameters is illustrated by experimental data. Abstract: Despite many studies and several extensive reviews of redox flow batteries (RFBs) over the last three decades, information on engineering aspects is scarce, which hinders progress with scale-up and implementation of this energy storage technology. This review summarises cell design requirements then critically considers design, construction and cell features together with their benefits and problems, leading to good practice through improved cell performance, knowledge and experience. Techniques for the characterisation of the reaction environment are illustrated by measurements of mass transport to (and from) electrode surfaces as a function of flow conditions, as well as pressure drop and electrolyte flow dispersion. The influence of design features on performance is illustrated by the effect of process conditions on the components of cell potential. Adequate attention to engineering aspects is seen to be critical to the effective performance of RFBs, particularly during scale-up and long-term operation. Techniques for the characterisation of reaction environment are summarised and a list of essential design and construction factors is provided. Finally, critical areas needing research and development are highlighted.